(untitled) (Veterinary Science Development, 2017)
No previous reports have described cardiopulmonary bypass (CPB) techniques involving long aortic cross clamp (ACC) times in small-breed dogs. We previously described open heart surgery under deep hypothermic CPB in small and toy dogs with an approximate ACC time limit of 1 hour, given the low success rate beyond 90 minutes of ACC time. Herein, we describe improvements in cardiac anesthesia, CPB, and cardioplegia that led to a high success rate of open heart surgery with a long ACC time in small dogs. Ten small-breed dogs with severe mitral regurgitation were subjected to mitral valve plasty that necessitated cardiopulmonary bypass (CPB) beyond 90 minutes of ACC time. In the present study, all dogs survived surgery; 7 survived to discharge. In other words, we achieved a high success rate of 70% with mitral valve plasty beyond 90 minutes of ACC time (mean, 105.1 minutes: range, 90-117 minutes). For small dogs, successful open heart surgery with a long ACC time may require cardiac balanced anesthesia, CPB with increased drainage and, importantly, thorough cardioplegia without hemodilution.